Perbandingan Niat Kewirausahaan Dan Efek Pendidikan Kewirausahaan Antara Mahasiswa Jurusan Manajemen Dan Akuntansi Fakultas Ekonomi Universitas Tarumanagara - Felicia Yulanda; Herlina Budiono (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
The purpose of this study was to examine the comparison of entrepreneurial intentions and the effects of entrepreneurship education between Management Department students and Accounting Department students at the Faculty of Economics, Universitas Tarumanagara. The sample was chosen by a nonprobabiliy sampling method of 100 respondents at the Faculty of Economics, Universitas Tarumanagara. Data processing techniques using IBM SPSS 23. The results of this study indicate that 1) in entrepreneurial intentions there is no significant difference between the Management Department Students and Accounting Department students at the Faculty of Economics, Universitas Tarumanagara. 2) in the effect of entrepreneurship education there is a significant difference between the Management Department students and Accounting Department students at the Faculty of Economics, Universitas Tarumanagara.Tujuan dari penelitian ini adalah untuk menguji perbandingan niat kewirausahaan dan efek pendidikan kewirausahaan antara mahasiswa Jurusan Manajemen dan mahasiswa Jurusan Akuntansi di Fakultas Ekonomi Universitas Tarumanagara. Sampel dipilih dengan metode nonprobabiliy sampling sebesar 100 responden di Fakultas Ekonomi Universitas Tarumanagara. Teknik pengolahan data menggunakan program IBM SPSS 23. Hasil penelitian ini menunjukkan bahwa 1) pada niat kewirausahaan tidak terdapat perbedaan yang signifikan antara Mahasiswa Jurusan Manajemen dan mahasiswa Jurusan Akuntansi di Fakultas Ekonomi Universitas Tarumanagara. 2)pada efek pendidikan kewirausahaan terdapat perbedaan yang signifikan antara mahasiswa Jurusan Manajemen dan mahasiswa Jurusan Akuntansi di Fakultas Ekonomi Universitas Tarumanagara.